Physical compatibility of ibuprofen and selected parenteral drugs during simulated y-site administration - Katarzyna Dettlaff; Katarzyna Dominiak; Marta Klimaszewska; Aleksandra Gostyńska (Polskie Towarzystwo Farmaceutyczne, 2023)
Intravenous ibuprofen (IBF) is indicated for short-term acute moderate pain and fever management. Limited data concerning the compatibility of intravenous IBF and other parenteral medications makes it inconvenient to use in polypharmacy-required patients. The simultaneous administration of two incompatible drugs is a health- or even life-threatening medical error. This study was performed to evaluate the physical compatibility of two intravenous IBF doses (600 mg/100 mL, 400 mg/100 mL) during Y-site administration with common parenteral medications. Eight infusion fluids, seven ready-to-use solutions for infusion, and thirty concentrates or powders for solutions for infusion were examined. All these drugs, if relevant, were reconstituted and diluted following the manufacturer's instructions to achieve concentrations found most commonly in clinical practice. Samples were prepared by mixing IBFs and selected drug product solutions at the 1:1 volume ratio. All samples underwent visual inspection and determination of pH and turbidity before combining with IBF and in time points (0, 30, 60, and 120 minutes) after simulated Y-site administration with IBF. In the case of propofol, which is an emulsion for infusion, lipid droplet size, zeta potential, and polydispersity index were also determined. The incompatibilities were observed for IBF combinations with amiodarone, ciprofloxacin, clemastine, gentamicin, vinpocetine, and calcium chloride.